2020
DOI: 10.1016/j.apsb.2019.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled natural phytochemicals for synergistically antibacterial application from the enlightenment of traditional Chinese medicine combination

Abstract: The application of nanotechnology for antimicrobial delivery has capacity to improve antibacterial efficacy. Currently, the usage of various inorganic and organic carriers, such as metal ions, nano-silicon and surfactants, might increase the potential toxicity of nanoparticles and make their clinical transformation more difficult. Herein, a nano-delivery system was constructed by direct self-assembly of antibacterial phytochemicals (berberine and rhein) originated from traditional Chinese medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 43 publications
3
80
2
Order By: Relevance
“…They carry potential biosensor and drug carrier properties [ 122 ]. Recently, the self-assembled small-sized phytochemicals (berberine and rhein) nanoparticles derived from TCM without nano adjuvant have shown prominent antibacterial activity against the S. aureus biofilm [ 123 ]. The combinational or synergistic effect of Chinese herbal AgNPs has promising therapeutic properties for targeted drug delivery systems and other extensive medical applications [ 124 , 125 , 126 ], biosensors and detection for anticancer treatment [ 127 ], and bioimaging [ 128 ].…”
Section: Antimicrobial Properties Of Chinese Herbsmentioning
confidence: 99%
“…They carry potential biosensor and drug carrier properties [ 122 ]. Recently, the self-assembled small-sized phytochemicals (berberine and rhein) nanoparticles derived from TCM without nano adjuvant have shown prominent antibacterial activity against the S. aureus biofilm [ 123 ]. The combinational or synergistic effect of Chinese herbal AgNPs has promising therapeutic properties for targeted drug delivery systems and other extensive medical applications [ 124 , 125 , 126 ], biosensors and detection for anticancer treatment [ 127 ], and bioimaging [ 128 ].…”
Section: Antimicrobial Properties Of Chinese Herbsmentioning
confidence: 99%
“…With the continuous development of supramolecular self-assembly technology, their application as a part of biomedically functional delivery vehicles has been proposed to construct in drug delivery system without any structural modification or organic solvent [ 22 , 23 ]. The delivery carriers produced by specific SMNPs not only have satisfactory safety but also have stimuli-sensitive characteristics to control the release of agents [ 24 ]. More importantly, SMNPs confer significant bioactive activities, which can further play a synergistic role to treat disease without the help of any additives [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, supramolecular assemblies in traditional medicines have received more attention because they can improve treatment efficacy and reduce toxicity. Inspired by natural supramolecular assembly, our previous studies have found a variety of self-assembled supramolecular structures, including hydrogels ( Li et al, 2019 ) ( Li et al, 2019 ), nanoparticles/microparticles ( Tian et al, 2020 ), and crystals ( Huang et al, 2019 ), formed through various combinations of traditional medicines. Most recently, we found that glycyrrhizic acid can self-assemble with compounds in Genkwa Flos to form a kind of spherical supramolecular structure ( Genkwa Flos /glycrrrhizic acid self-assembled complex), which had not been detected in previous studies of their mechanism or chemical composition.…”
Section: Introductionmentioning
confidence: 99%